Early Changes of VEGF Levels After Zoledronic Acid in Women With Postmenopausal Osteoporosis: A Potential Role of Vitamin D - Bellone, Federica; Catalano, Antonino; Sottile, Angelo Ruggero; Gaudio, Agostino; Loddo, Saverio; Corica, Francesco; Morabito, Nunziata (Frontiers in Medicine, 2021)
Zoledronic acid (Zol) is a widely used intravenous aminobisphosphonate to treat both benign and malignant skeletal diseases, and bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a serious side effect whose pathophysiology remains poorly understood. Vascular Endothelial Growth Factor (VEGF) has been recognized to mediate BRONJ in cancer patients undergoing Zol treatment, however data on VEGF are lacking in patients with osteoporosis. Increasing evidences demonstrate that vitamin D influences VEGF levels. The aim of this study was to investigate the influence of Zol on VEGF levels and the possible role for vitamin D on the Zol mediated changes of VEGF concentration in women with postmenopausal osteoporosis. 28 postmenopausal women with osteoporosis were enrolled and randomized into 2 groups to receive Zol (5 mg) or placebo. At baseline, at day-3 and day-30 VEGF serum levels were measured; bone turnover markers, 25-hydroxyvitamin D (25(OH)D) and serum calcium were evaluated at baseline. In Zol-treated women, VEGF increased significantly on day-3, and then decreased on day-30. In the Zol-treated women, the percent change of VEGF levels between baseline and day-30 (-18% at day-30 vs. baseline, p=0.01) was significantly associated with serum 25(OH)D values (r= 0.29, p= 0.028). At a stepwise multiple regression analysis, after correcting for age, BMI, time since menopause, femoral neck BMD, osteocalcin, C-terminal telopeptide of type 1 collagen and baseline VEGF levels, 25(OH)D levels were independently associated with VEGF change (β= 1.7, SE= 0.71, p=0.03). For the first time, we detected early modifications of circulating VEGF in postmenopausal women receiving Zol for osteoporosis, identifying a vitamin D-dependent modulation of these changes.